(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Porana paniculata (Convolvulaceae) is a much -branched extensive twiner of varied therapeutic value. The antioxidant activity of its leaf extract was evaluated. The extraction was carried out by maceration using water and ethanol as a solvent and then total flavonoid and total phenol content was determined by standard methods.